2018
DOI: 10.1002/jcb.28297
|View full text |Cite
|
Sign up to set email alerts
|

Polydatin suppresses the development of lung inflammation and fibrosis by inhibiting activation of the NACHT domain‐, leucine‐rich repeat‐, and pyd‐containing protein 3 inflammasome and the nuclear factor‐κB pathway after Mycoplasma pneumoniae infection

Abstract: Mycoplasma pneumoniae (MP) can infect both the upper and lower respiratory tracts. Polydatin (PD), a traditional Chinese medicine, is known to have anti-inflammation and antifibrosis properties. However, the protective effects of PD against MP pneumonia (MPP) remain unclear. So, the aim of this study was to describe the therapeutic effects and underlying mechanisms of PD against MPP. BALB/c mice were assigned to three groups: a normal control group, MP infection group, or PD-treated MP infection group. BEAS-2B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Although the induction of the NLRP3 inflammasome contributes to host defenses against infections, dysregulated inflammasomes are associated with many human diseases, such as cancer, autoimmune diseases, and inflammatory disorders [[29], [30], [31], [32],66]. Our findings that G6PD inhibition can attenuate inflammasome activation suggest a new approach for therapeutic intervention of inflammasome-associated diseases [67,68] with inflammasome as a target. Hence, a G6PD inhibitor such as Polydatin, might be considered as a therapeutic agent to attenuate inflammasome-associated diseases [67,68].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although the induction of the NLRP3 inflammasome contributes to host defenses against infections, dysregulated inflammasomes are associated with many human diseases, such as cancer, autoimmune diseases, and inflammatory disorders [[29], [30], [31], [32],66]. Our findings that G6PD inhibition can attenuate inflammasome activation suggest a new approach for therapeutic intervention of inflammasome-associated diseases [67,68] with inflammasome as a target. Hence, a G6PD inhibitor such as Polydatin, might be considered as a therapeutic agent to attenuate inflammasome-associated diseases [67,68].…”
Section: Discussionmentioning
confidence: 78%
“…Our findings that G6PD inhibition can attenuate inflammasome activation suggest a new approach for therapeutic intervention of inflammasome-associated diseases [67,68] with inflammasome as a target. Hence, a G6PD inhibitor such as Polydatin, might be considered as a therapeutic agent to attenuate inflammasome-associated diseases [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…An inflammasome represents a multi-protein complex that protects the host against the invading pathogens through induction of proinflammatory factors, among which the NLRP3 inflammasome plays the most important role [25,45,46]. The NLRP3 inflammasome complex is comprised of NLRP3, ASC and caspase-1 [45].…”
Section: Discussionmentioning
confidence: 99%
“…A study has demonstrated that polydatin improves lipopolysaccharide (LPS)-induced acute respiratory distress syndrome (ARDS). In addition, polydatin has mediated Parkin-dependent mitophagy and protects against mitochondria-dependent apoptosis in ARDS [209,210] niae (MP) infection, MP can infect both the upper and lower respiratory tracts, was found to be suppressed by polydatin treatment through inhibition of the NACHT domain-, leucinerich repeat-, and pyd-containing protein 3 inflammasome (NLRP3) and the nuclear factor-κB pathway after MP infection [211]. Actually, several in vivo studies have reported an important protective role of polydatin treatment via different mechanisms in ovalbumin-induced bronchial asthma as well as in LPS-induced acute lung injury [212,213].…”
Section: Polydatinmentioning
confidence: 99%